Petroleum Wealth Management in Emerging and Developing Countries - Abugre, James; Abor, Joshua; Salim, Ruhul; Ofori-Sasu, Daniel (Routledge, 2023)
The avoidance of a natural resource curse is incumbent on the exploration process and management of the wealth that comes from the resource. This chapter examines how emerging and developing countries utilise and manage their petroleum wealth for the benefit of their citizens. The approaches and principles that have been employed in other jurisdictions to manage petroleum wealth have been discussed and analysed. Challenges of petroleum wealth management including, corruption, neglect of other critical sectors of national economies, and environmental and social nuisances are examined. Transparency and accountability, a free society and stable democracy, legislation and policy direction, equitable distribution of petroleum wealth and conscious investment into equally important sectors such as agriculture, service and manufacturing are identified as key variables and strategies that must be embraced if emerging and developing countries are to maximize their petroleum resources to improve the living standards of their people.